Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/cssc.201701648
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective and Catalyst‐Free O‐Borylation of Silanols: A Facile Access to Borasiloxanes

Abstract: This paper demonstrates the first highly chemoselective syntheses of various borasiloxanes from hydroboranes and silanols, achieved through catalyst-free dehydrogenative coupling at room temperature. This green protocol, which uses easily accessible reagents, allows for the obtaining of borasiloxanes under air atmosphere and solvent-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Prior to our communication, a handful of catalysed processes relying on late‐transition‐metal complexes, Sc(OTf) 3 or Mo(CO) 6 had been shown to yield borasiloxanes upon coupling of silanols or hydrosilanes with hydroboranes, diboranes, boraxanes, allylborane or vinylboronates. In a reversed and complementary methodology to borinic acid‐hydrosilane dehydrocoupling, silanols and pinacol‐ and catecholborane can also be coupled in the absence of specific catalyst . The known processes for the production of borasiloxanes are summarised in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Prior to our communication, a handful of catalysed processes relying on late‐transition‐metal complexes, Sc(OTf) 3 or Mo(CO) 6 had been shown to yield borasiloxanes upon coupling of silanols or hydrosilanes with hydroboranes, diboranes, boraxanes, allylborane or vinylboronates. In a reversed and complementary methodology to borinic acid‐hydrosilane dehydrocoupling, silanols and pinacol‐ and catecholborane can also be coupled in the absence of specific catalyst . The known processes for the production of borasiloxanes are summarised in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Urban land use includes industrial hubs, residences, major infrastructure such as ports, and other uses designed to support concentrated human settlement. While these activities are heterogeneous, they often spatially covary and are evaluated together under proxies like Total Impervious Area or the Landscape Development Intensity Index (Brabec et al, 2002;Brown and Vivas, 2005;Dadhich et al, 2017). Urban land use affects corals through a number of pathways, including (1) habitat loss from nearshore earthmoving, (2) industrial pollution from factories and power plants, (3) untreated sewage from both sewer outfalls and underground storage tanks, (4) stormwater runoff from impervious pavement, (5) marine debris and artificial substrates, and (6) impacts of artificial light on reef organisms like zooplankton, polychaete worms, and reef fish (Aubrecht et al, 2008;DeGeorges et al, 2010;Suchley and Alvarez-Filip, 2018).…”
Section: Urban Land Usementioning
confidence: 99%
“…Both of them provide the process to some extent following green chemistry aspects. Recently, our group developed some of procedures utilizing pinacolborane (HBPin) in O ‐borylation of silanols/polyhedral oligomeric silsesquioxane silanols (POSS silanols), and hydroboration of carbonyls. [5u], [6d] Our studies have shown that aldehydes can be efficiently transformed into their boronic ester derivatives under catalyst‐free and solvent‐free conditions (mostly at elevated temperature).…”
Section: Figurementioning
confidence: 99%